PERAN LAGU TANAH AIRKU KARYA IBU SUD SEBAGAI MEDIA PENANAMAN NILAI TOLERANSI DAN IDENTITAS BUDAYA BANGSA: Peran Lagu Tanah Airku Karya Ibu Sud Sebagai Media Penanaman Nilai Toleransi Dan Identitas Budaya Bangsa - Iqlimah Amalia; Neni Triana; Tsabita (Institut Agama Islam Sumatera Barat Pariaman, 2025)
Indonesia, as a multicultural nation with diverse ethnicities, languages, and traditions, requires unifying instruments to strengthen its national identity. National songs serve not only as works of art but also as tools for character education and symbols of nationhood. This study aims to analyze the role of Tanah Airku by Ibu Sud in instilling tolerance and reinforcing cultural identity. The research employs a qualitative approach through a literature review of books, journal articles, and relevant documents related to national songs, multicultural education, and nationalism. The findings reveal that the simple yet meaningful lyrics of Tanah Airku evoke deep love for the homeland, loyalty, and unity. Furthermore, the song fosters tolerance by embracing ethnic, cultural, and religious differences within one shared identity, thereby reinforcing nationalism and representing peace.